Decline in match running performance in football is affected by an increase in game interruptions - Linke, D.; Link, D.; Weber, H.; Lames, M. (Journal of Sports Science & Medicine, 2018)
This study quantified the contribution of game interruptions to the fatigue-related declines in match running performance over the course of a football match. Using a semi-automatic multiple camera system, the running activity of 792 individual German Bundesliga performances was divided into pre-defined 15-minute intervals and subsequently analysed under two prerequisites: with (effective playing time) and without (total playing time) consideration of game interruptions. Results showed a significant decline in effective playing time over the course of a match, from 66.3% of the total playing time in the first 15 minutes to 55.9% in the final 15 minutes of a match. Under consideration of the total playing time, match running performances decreased by 24.2% on average; considering the effective playing time, they decreased on average by only 10.2%. It can, therefore, be concluded that more than half (57.9%) of the commonly reported decline in match running performance cannot be assigned to physical fatigue, but rather to an increase in game interruptions as the game progresses. In conclusion, this study demonstrated for the first time that the decline in players` match running performance during football matches is substantially amplified by a proven increase in game interruptions, indicating that there may be a tendency among practitioners to overestimate fatigue-induced performance declines.